Calculated stabilities and structures for carbocations and singlet carbenes bearing electron‐withdrawing groups†. (10th July 2013) - Gronert, Scott; Keeffe, James R.; Page, Michael I.
<x xml:space="preserve">Abstract</x> Carbocations and carbenes, as electron‐deficient species, require electron donation from the remainder of the molecule to the carbon center by whatever means available. Classical interactions include resonance, polar and polarizability effects, but neighboring group participation of several sorts can also serve as stabilizing factors. Simple carbocations with directly attached electron‐withdrawing groups (EWGs), that is, EWG–CH2+ ions, comprise one group by which these interactions may be probed. This article provides computational evidence at the MP2/6‐311 + G** level for variable but significant stabilizing interactions between the carbocation center and common EWGs, many via bridging (partial or symmetrical), neighboring group participation, homoconjugation or π interactions. Bridging from atoms possessing nonbonding electron pairs is a common motif. Removal of bridging by application of geometric constraints nullifies bridging stabilization, but does not eliminate the possibility of other stabilizing interactions, for example polar, polarizability and π donation from the EWG. The potential for π donation from strong EWGs has not been widely appreciated in the past. A carbocation stabilization enthalpy, CSE+, is defined as the enthalpy of the isodesmic reaction CH3+ + R–H → CH4 + R+. Comparisons are made with singlet carbenes bearing EWGs for which many structural features are similar. Copyright © 2013 John Wiley & Sons, Ltd.